Diagnostics of biological compounds by optical resonator matrices - A. V. Saetchnikov; E. A. Tcherniavskaia; V. A. Saetchnikov; A. .. Ostendorf (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The mechanism of biochemical compounds diagnostics using matrices based on optical resonance in closed dielectric microcavities is discuss in this paper. A method for sensor fabrication, interrogation of the optical elements as well as approach for spectral data processing are represented. Experimental data of the protein molecules detection using a matrix sensor in the photonic and photonic-plasmonic configurations is realized.